Mandibular Ameloblastic Carcinoma in a Boxer Bitch - Lopes de Oliveira Pozeti, Catarina; Santana da Silva, Stefanie Tenille; Teixeira Damasceno, Breno; Giberne Ferro, Daniel; Lessa Abdalla, Samira (Acta Scientiae Veterinariae, 2025)
Background: Ameloblastic carcinoma is a malignant tumor of the odontogenic epithelium, extremely uncommon in veterinary medicine. The diagnosis was made after preoperative histopathological evaluation of incisional biopsy and the definitive diagnosis was confirmed with histopathological evaluation, in which the surgical margins showed no neoplasic cells. However, a better prognosis was observed for tumors with surgical margins free of neoplasmatic cells, located in the rostral region of the mandible. The aim of this paper is to report a case of ameloblastic carcinoma located in the rostral region of the left mandible in a 8-year-old spayed bitch Boxer. Case: In this report, treatment of ameloblastic carcinoma was carried out, based on the veterinary literature. Using surgical resection, unilateral rostral mandibulectomy was performed on the left region, with a wide surgical margin. An intraoral radiograph (X-ray) was also performed to visualize bone lysis, demonstrating tumor invasion in the rostral mandibular bone. Electrochemotherapy was administered trans-surgically to widen the surgical margins. Periodontal treatment and gingivectomy were also carried out to decontaminate the surgical site and reduce postoperative risks. The patient has been assisted by an oncology specialist and has shown no signs of local recurrence, new neoplastic sites or metastasis, up to the end of the present study. Discussion: The case describe highlights the rarity and aggressiveness of mandibular ameloblastic carcinoma in dogs. In dogs, the oral cavity is the 4th most common site of neoplasms. There is no defined breed or gender preference, but it has been reported that many purebred dogs have a higher risk of developing oral tumors, including Boxer dogs. Only 4 cases have been reported in veterinary medicine to date. Ameloblastic carcinoma still has a guarded prognosis, due to the small amount of related literature. This emphasizes the importance of detailed histopathological diagnosis and surgical intervention with clear margins. The adjuvant use of electrochemotherapy contributed to local tumor management. Despite the complexity of differential diagnosis and the reserved prognosis, the patient had a favourable outcome, with no signs of metastasis or recurrence after 9 months, highlighting the importance of regular clinical follow-up. Electrochemotherapy as a therapeutic modality is fully indicated in both human and veterinary oncology clinics. Current literature already reports its use in oral neoplasms with good results. To date, no literature has reported the use of electrochemotherapy specifically for ameloblastic carcinoma. However, the use of this method was considered as an adjuvant in the reported case, due to the in situ aggressiveness demonstrated by the ameloblastic carcinoma, in order to increase the surgical safety margin. The conclusion of this study emphasizes that ameloblastic carcinoma is a rare tumor in veterinary medicine, with limited literature on its incidence and treatment. Although odontogenic tumors are generally infrequent, oral tumors have a higher incidence. Regular inspection of the oral cavity during dental consultations is essential for detecting tumors in the early stages, offering a more favorable prognosis for patients. Keywords: dogs, mandibular neoplasia, odontogenic tumors, ameloblastoma, mandibulectomy. Título: Carcinoma ameloblástico mandibular em uma cadela Boxer Descritores: cães, cavidade oral, ameloblastoma, carcinoma ameloblástico, tumores odontogênicos.